Comparison of cartilage thickness with radiologic grade of knee osteoarthritis - Agnesi, Filippo; Amrami, Kimberly K.; Frigo, Carlo A.; Kaufman, Kenton R. (Skeletal radiology, 2008)
Objective To compare joint space width (JSW) measurements obtained from magnetic resonance imaging (MRI) with a semi-automated computer algorithm to the Kellgren and Lawrence grading of osteoarthritis (OA). Materials and methods Three hundred and six patients (234 female, 72 male) with a mean age of 56.7 years (range 31–81 years) underwent MRI of their knees with a fast oblique spiral spoiled gradient (SPGR) sequence. A board-certified musculoskeletal radiologist graded the OA of all the patients in accordance with the Kellgren and Lawrence OA scale. A previously validated computer algorithm was used to determine the minimum JSW for both the tibiofemoral joint and the patellofemoral joint. An analysis of variance (ANOVA) with the Student–Newman–Kuels post-hoc test was used to determine if there were differences in JSW as a function of OA grade. Results The radiologic grade of OA was inversely associated with the JSW. In the medial compartment the JSW did not change significantly between grade 1 and grade 2, but there was a significant decrease in JSW between grade 0 (normal) and grade 1 and for each OA grade above grade 2. In the lateral compartment no statistical differences were found till grade 2, while grade 3 was found to be statistically different from the previous one. The number of patients with a grade 4 patellofemoral OA was too low for the statistical significance to be assessed. In the patellofemoral joint the JSW did not change significantly until grade 2, while a statistically significant reduction was found for both grade 3 and grade 4. Conclusion This study showed that an inverse non-linear relationship exists between radiologic grade and JSW. The relationship differs for the tibiofemoral and the patellofemoral joint.